Trunk motion during a half-marathon: the impact of perceived fatigue on motion stability and smoothness - Apte, S.; Laroche, N.; Gremeaux, V.; Aminian, K. (ISBS Proceedings Archive (Michigan), 2022)
Our objective was to investigate the effects of acute fatigue on stability and smoothness of trunk motion during a half marathon. 13 recreational runners were fitted with a GNSS-IMU sensor on their chest. Every 10 minutes of the race, the participant pronounced their perceived fatigue, recorded by a smartphone attached to the arm. We divided the race into 8 equal segments, corresponding to one fatigue score per segment, and considered only level running. Based on mediolateral acceleration and running velocity (v), stability was characterized by spectral entropy, RMS of acceleration (RMSA), and autocorrelation between successive steps and strides; smoothness by jerk cost (JC), spectral arc length (SPARC), and inverse number of peaks (IPV) of v. Both RMSA and JC increased significantly shortly after race onset. RMSA increased significantly at a lower perceived fatigue level, while JC increased at a higher level. Whereas other measures did not change substantially, RMSA and JC showed a clear change with acute fatigue and also differentiated well between the five fastest and five slowest runners. With increasing perceived fatigue, both parameters showed a higher change for `slow` group. This study highlights the loss of stability and smoothness in running due to acute fatigue and the importance of simultaneously measuring perceived fatigue and trunk biomechanics under real-world conditions.